Two-Dimensional Titanium and Molybdenum Carbide MXenes as Electrocatalysts for CO2 Reduction - Albertus D. Handoko; Hetian Chen; Yanwei Lum; Qianfan Zhang; Babak Anasori; Zhi Wei Seh (iScience, 2020)
Summary: Electrocatalytic CO2 reduction reaction (CO2RR) is an attractive way to produce renewable fuel and chemical feedstock, especially when coupled with efficient CO2 capture and clean energy sources. On the fundamental side, research on improving CO2RR activity still revolves around late transition metal-based catalysts, which are limited by unfavorable scaling relations despite intense investigation. Here, we report a combined experimental and theoretical investigation into electrocatalytic CO2RR on Ti- and Mo-based MXene catalysts. Formic acid is found as the main product on Ti2CTx and Mo2CTx MXenes, with peak Faradaic efficiency of over 56% on Ti2CTx and partial current density of up to −2.5 mA cm−2 on Mo2CTx. Furthermore, simulations reveal the critical role of the Tx group: a smaller overpotential is found to occur at lower amounts of –F termination. This work represents an important step toward experimental demonstration of MXenes for more complex electrocatalytic reactions in the future.